TERRITORIAL FACTOR IN FORMING VALUE SPHERE OF THE YOUTH - E. M. Dumnova (Вестник Кемеровского государственного университета, 2014)
The paper considers the problem of forming family values in the aspect of external factorsinfluence. A comparative sociological analysis of Novosibirsk students’ value sphere is presented. A sociological study, conducted in February 2013, addressed students of four Novosibirsk universities. The sample included 453 people. The quota type of the sample was used. The study employed the author’s research tools (questionnaires). The paper presents the data concerning two groups of respondents: Novosibirsk city residents and residents of other towns (rural areas). The influence of the circumstances of initial socialization on the youth’s values and mentality formation is analyzed. The study made it possible to formulate a number of original conclusions concerning the role of the territorial factor in the choice of the key of life strategy and in the process of mentality formation in various youth groups in general. The general trend of the student youth value formation, reflecting a high importance of traditional values, is revealed. At the same time, a significant difference in their life strategies is discovered. The youth, brought up in the urbanized social space, chooses the diachronic key of life strategy. The country youth, having moved to the city, chooses the synchronic key.